(NkONE^NYE \LEMENTY I APPROKSIMACIQ (B/s - (NzENKEWI^(B, (NoLXGERDs; (NmORGAN(B, (NkENNETs; (NkWASOW(B, (Nb(B.(Ni(B.s ((NmOSKWA (B:s (NmIR(B,s, 1986)
(NbIBLIOGR(B.: (NS(B. 304-305s
(NuKAZ(B. (NIMEN(B. (NI PREDM(B.: (NS(B. 306-315s
Keywords: (NaPPROKSIMACIQ (B((NMAT(B.)s; (NkONE^NYH \LEMENTOW METODs